Paparan Gadget pada Usia Dini sebagai Faktor yang Berhubungan dengan Perkembangan Anak Usia Dini - Brivian Florentis Yustanta; Dwi Ertiana; Dewi Taurisiawati Rahayu (STIKES Karya Husada Kediri, 2026)
Gadget use in early childhood continues to increase with the development of digital technology. Data shows that approximately 60–70% of preschool-aged children use gadgets daily, and more than 30% experience usage durations exceeding recommendations. Excessive gadget use has the potential to reduce social interaction and opportunities for optimal stimulation, thus impacting motor, language, social, and independence development. This study aims to analyze the relationship between gadget exposure at an early age and the development of children aged 1–3 years. The study used a correlational analytical design with a cross-sectional approach. The study was conducted at the Asmorobangun Village Integrated Health Post (Posyandu) from May 13–26, 2025. The study population consisted of 98 children aged 1–3 years. A sample of 79 respondents was selected using a simple random sampling technique. Data on gadget use and child development were collected using questionnaires and the Pre-Screening Development Questionnaire (KPSP). Data analysis was performed using the Spearman Rho test with a significance level of α = 0.05. Most respondents had moderate levels of gadget use. Twenty-one children (26.6%) were found to have questionable development. The Spearman's Rho test results showed a p-value of 0.000 and a correlation coefficient of r = -0.706. These findings indicate a significant relationship between gadget use and the development of children aged 1–3 years, with a strong correlation and a negative direction. Children with higher levels of gadget use tend to experience more questionable and deviant development than children with lower levels of gadget use. Therefore, parental supervision and guidance are necessary regarding children's gadget use.